Core Competencies in Agripreneurship: A Scoping Review - Alexis Zickafoose; Jera Niewoehner-Green; Rafael Landaverde; Mary Rodriguez (Journal of International Agricultural and Extension Education, 2026)
Agripreneurship is frequently included in programs and research that aim to increase communities’ economic development. This scoping review aims to understand how agripreneurship is operationalized in research and practice. We analyzed 76 studies that were conducted across 97 countries to determine their research practices and the competencies they examined. The results showed the studies examine agripreneurial competencies, agripreneurial system, agripreneurial outcomes, agripreneurial training, and knowledge generation. Agripreneurship is operationalized through the core competencies of agripreneurship. The core competencies identified were business skills, characteristics, social skills, knowledge, other skills, communication skills, external supports, agricultural skills, values, and background. Integrating all these competencies in agripreneurship interventions and research could increase the ability of participants to start and maintain their enterprise.
Keywords: rural entrepreneurship; economic development; enterprise; international development; small and medium enterprises